Long-term Measurements of PM2.5 Concentrations in Lubbock, Texas - Mary C. Kelley; Mallory M. Brown; Clifford B. Fedler; Karin Ardon-Dryer (Aerosol and Air Quality Research)
Abstract Aerosol particles, such as PM2.5 (particulate matter with an aerodynamic diameter ≤ 2.5 µm), are an important yet variable component of our atmosphere; their presence defines the air quality and profoundly affects human health. In this project, we examine changes in the PM2.5 concentration, which is subject to temporal and spatial conditions and may vary by hour or day, in Lubbock, Texas, from 2001 to 2018. The hourly PM2.5 concentrations were measured at the local Texas Commission on Environmental Quality (TCEQ) station, analyzed for diurnal, weekly, monthly, seasonal, and yearly changes, and compared with meteorological parameters (such as the temperature, wind direction or speed, and visibility) recorded by the local National Weather Service station at Lubbock Preston Smith International Airport. In addition, we examined the effects of El Niño and La Niña on the PM2.5 concentration. The majority of the average daily PM2.5 values fell below the Environmental Protection Agency (EPA) daily threshold of 35 µg m−3, but many days exhibited high hourly concentrations, mainly due to dust storm events. No correlations were found between the concentrations and various meteorological parameters. Based on the hourly measurements, the diurnal distributions were bimodal, with morning and evening peaks, and the highest monthly averages were observed for April and June. A comparison of the PM2.5 concentrations during El Niño and La Niña revealed higher values during the latter, with the maximum concentrations occurring during weak La Niñas.